Concerning the Dating of Two Graves at the Baitai Burial Ground - Banytė, Rasa (Archaeologia Lituana, 1999)
The article discusses artefacts from two women’s graves relatively well-endowed with funerary goods that were excavated at Baitai (Klaipėda District) in 1991. This burial ground belongs to the Western-Lithuanian-stone-circle graves’ culture. Research carried out in 1989–1991, 1993 and 1995 have revealed material from the second half of the Old Iron Age (the “Roman Period”). Excavations continue, but there remains insufficient evidence to clarify the site’s whole chronology and therefore, this article compares two Baitai women’s graves (see ill. 1, 2) with each other and with material from other sites in Western Lithuania. In Baitai women’s graves 8 and 18 and other women’s graves from western Lithuania we find artefacts which are numbered hever in an order particular to this text. This article compares Baitai 8 and 18 with Šernai 10 and 22, Bandužiai 85, Lumpėnai 14, which in addition other common artefacts include iron bell-shaped pendants among their gravegoods. The following artefacts and their chronology are discussed here: hats decorated with studs and hooked pendants, and headbands; necklaces with spiral terminals; necklaces with amber, glass beads and iron bell-shaped pendants; rosette pins or brooches with profiled studs and concentric strands; large cross-bow brooches with a bent foot and small rings (or not); smaller cross-bow brooches with a bent foot and slightly protruding bows; a cross-bow brooch with a rhomboid foot; spiral bracelets typical of the Klaipėda district; bracelets with slightly thickened terminals; rings with a flattened rhomboid front part; rings with overlapping terminals. Although there is not doubt that we must research and compare Baitai gravegoods more deeply, the Author is inclined at present to date Baitai 8 and 18 to the C3 Period (A.D. 300–350 and later).